PERTUMBUHAN EKONOMI DAN INFLASI TERHADAP NON PERFORMING FINANCING PADA BANK UMUM SYARIAH DI INDONESIA - Muhammad Nasir; muhammad Nasir; Rusdy Rusdy; Nova Eliza (Politeknik Negeri Lhokseumawe, 2021)
This study aims to determine the effect of economic growth and inflation on non performing financing on sharia commercial banks in Indonesia. This research only discusses external factors such as economic growth and inflation. The data used in this research are monthly publication by Indonesia Bank and sharia banking statistics publication by Financial Services Authority on period January 2014 until December 2018. The data analysis method used in this study is multiple linear regression analysis using SPSS. The results of this study indicate that simultaneously economic growth and inflation have significant effect on non performing financing . and then, partially economic growth and inflation have a negative and significant effect on non performing financing. This research recommends to the monetary authority in order to maintain the stability of the economics growth and inflation that be able to encourage the development of Sharia banks in the future.Keywords: Non Performing Financing (NPF), Economic Growth, and Inflation